Local Raw Materials Waste-Based Paper Production Technology - Z. K. Galimova; N. X. Tursunbaeva (Scientific Trends, 2024)
Paper is the most important basic material in the creation of printing products. The basis of the structure of paper is a frame made of fibrous bodies. Papermaking is the production of paper and cardboard, widely used in writing, printing and packaging. The article demonstrates the possibility of extracting cellulose from unused soybean stalks to develop paper and cellulose production. Paper samples with high mechanical strength and whiteness were obtained.
Keywords: Paper structure, cellulose, mechanical strength, whiteness level, soybean, semi-finished product.